Role of Accounting Information Quality in Recency Bias in Investors’ Behavior - Sedighe Kamranrad (Shahid Bahonar University of Kerman, 2020)
Objective: This study examined the presence of the phenomenon of recency and the role of accounting information quality in the recency manifestation, concentrating on capital market mechanism with the use of accounting information. Method: In this study, earning per share, return on assets, return on equity and book value per share were used as indicators for accounting information. The method of data analysis was inferential. To test the research hypotheses, panel data multiple regression model and data of 148 companies in the Tehran Stock Exchange during 2008-2017 were used. Results: The findings showed that accounting information quality mitigates the recency phenomenon in investors behavior in the Iranian capital Market. Conclusion: By improving the quality of accounting information reported by companies, behavioral bias in investing decision making cab be reduced.